A green approach for the reduction of representative aryl functional groups using palladium ecocatalysts. Issue 2 (3rd April 2021) - Grison, Claude; Adler, Pauline; Deyris, Pierre-Alexandre; Diliberto, Sebastien; Boulanger, Clotilde
ABSTRACT: The reduction of functional groups has been thoroughly explored in organic synthesis. Nevertheless, most of the existing methodologies are based on conditions far from being environmentally friendly, which limits their usefulness. Here we report a green approach for the reduction of representative aryl functional groups using Eco-Pd catalysts. The Eco-Pd catalysts were prepared from palladium enriched vegetal filters that biosorbed palladium from an aquatic environment. The Eco-Pd catalysts were characterized by MP-AES XRPD and XPS, and used in the reductions of aryl halides, aryl aldehydes and nitroarenes in green conditions. A mixture of glycerol and n -butanol was used, as the solvent system and as the reducing reagent, in the presence of non-hazardous inorganic bases and without any ligands. Although Eco-Pd catalysis within this solvent system was homogeneous, we were able to recover and reuse the ecocatalyst to efficiently catalyze new reduction reactions. GRAPHICAL ABSTRACT: UF0001